Diastolic Abnormalities in Normal Phenotype Hypertrophic Cardiomyopathy Gene Carriers: A Study Using Speckle Tracking Echocardiography. Issue 5 (10th December 2012) - Kauer, Floris; van Dalen, Bas M.; Michels, Michelle; Soliman, Osama I. I.; Vletter, Wim B.; van Slegtenhorst, Marjon; ten Cate, Folkert J.; Geleijnse, Marcel L.
<x xml:space="preserve">Abstract</x> Background Tissue Doppler imaging (TDI) of the mitral annulus has been proposed as an alternative for the identification of hypertrophic cardiomyopathy (HCM) genetically affected subjects without left ventricular hypertrophy (G+/LVH−). Unfortunately, conflicting results have been described in the literature, potentially caused by the angle‐dependency of TDI. This study sought to assess abnormalities in mitral annular velocities in G+/LVH− subjects as detected by speckle tracking echocardiography (STE). Methods The study population consisted of 23 consecutive genotyped family members without major or minor criteria for the diagnosis of HCM (mean age 37 ± 13 years, 9 men) and 23 healthy volunteers (age 38 ± 12 years, 12 men) who prospectively underwent STE. Results There were no significant differences in global peak systolic annular velocity (7.4 ± 1.2 vs. 7.1 ± 1.0 cm/sec) and early diastolic annular velocity (10.2 ± 2.5 vs. 11.3 ± 2.2 cm/sec) between G+/LVH− and control subjects. Global peak late diastolic annular velocity was higher in G+/LVH− subjects (8.1 ± 1.7 vs. 5.7 ± 1.1 cm/sec, P < 0.001). Regionally, this difference was seen in all 6 studied LV walls. Conclusions This STE study confirms our previous TDI observations on increased peak late diastolic annular velocities in G+/LVH− subjects. Because of the complete overlap in early diastolic annular velocities this parameter cannot be used in the genotypes we studied to differentiate genotype (+) from genotype (−) individuals.